Holistic approach needed to address nursing shortage - Devi, Subramaniam * (MalaysiaKini, 2023)
Nurses, often considered the backbone of our healthcare system, have showcased their pivotal role in patient care, health promotion, and disease prevention even more prominently during the Covid-19 pandemic.